Novel design of a simple control system for hybrid electric motorcycle - Didi Widya Utama; Hadian Satria Utama; Reno Wardy (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2025)
A hybrid system combines two or more propulsion systems, typically including electric motors and internal combustion engines. In this research, the motorcycle uses a 5.67 kW/8000 rpm gasoline internal combustion engine and a 1 kW/48 V DC brushless electric motor, both coupled to an in-wheel electric motor. The control system was designed to automatically manage two propulsion systems based on the rotation speeds of an internal combustion engine and an electric motor, along with readings from current and voltage sensors. It uses two ATmega16-based microcontrollers, a master and a slave, and is monitored via Bluetooth using an Android smartphone. An experimental setup was conducted to effectively operate the system, utilizing the motorcycle in three modes: engine mode, electric motor mode, and hybrid mode, which demonstrated successful functionality through automatic propulsion displacement.